How Do Transcatheter Heart Valves Fit in Mitral Annuloplasty Rings and Which Combination Can be Recommended? - Ostovar, Roya; Kuehnel, Ralf-Uwe; Erb, Michael; Hartrumpf, Martin; Claus, Thomas; Haase, Robert; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Transcatheter heart valve (THV) as valve-in-ring is increasingly used in the mitral position. Semi-rigid rings may serve as a more appropriate scaffold for proper anchoring of a THV as they may change from their oval to a round shape thereby fitting to the implanted THV.Methods One rigid and five semi-rigid rings of four manufacturers, Edwards Physio I and II, Sorin 3D Memo, Medtronic Simulus, and St. Jude Medical (SJM) Saddle and SJM Sequin, with sizes 28 to 36 mm and Edwards Sapien III THV 23, 26, and 29 mm were used. Preevaluation comprised insertion/inflation of the THV into the ring and visual inspection for the paravalvular gap ≥ 4 mm2. Only valves not showing paravalvular gap were then submitted to hemodynamic evaluation with a pulse duplicator. Cusp movement was assessed with a high-speed-camera. Mean transvalvular gradients (TVGs) were measured.Results SJM Saddle ring of all sizes and SJM Sequin ring 34 showed marked gaps combined with all THV sizes, thus not undergoing hemodynamic testing. It was further shown that ring sizes ≥ 36 mm did not allow for a proper fit of even the largest THV into the ring of all the manufacturers and were consequently not hemodynamically evaluated. The 23 mm THV was too small for any ring size. The lowest gradients were achieved with the 26 mm THV in 30 and 32 mm and the 29 mm THV in 32 and 34 mm rings.Conclusion Not all currently available annuloplasty rings are ideal scaffolds for THV placement. It appears that a more proper fit can be achieved with semi-rigid rings than with rigid ones. Note that 23 mm THV appeared to be too small for an adequate anchoring in even the smallest available ring. Thus, 26 mm as well as 29 mm THV fit properly in ring sizes between 28 and 34 mm. Surgeons may consider to choose from those ring brands and sizes which allow for good placement of a THV in view of possible valve degeneration in the later course.
Keywords: valve-in-ring; transapical mitral valve implantation; mitral annuloplasty ring; heart valve; transapical; percutaneous (TAVI); rigid versus semi-rigid annuloplasty ring